Respuesta :
Answer:
x= −20
Step-by-step explanation:
Let's solve your equation step-by-step.
−3(x+9)=33
Step 1: Simplify both sides of the equation.
−3(x+9)=33
(−3)(x)+(−3)(9)=33(Distribute)
−3x+−27=33
−3x−27=33
Step 2: Add 27 to both sides.
−3x−27+27=33+27
−3x=60
Step 3: Divide both sides by -3.
−3x −3 = 60 −3 x=−20
Answer:
x=−20
Hope this helps! :)
Answer:
x=-20
Step-by-step explanation:
−3(x+9)=33
Divide both sides by -3
-3(x+9)/-3=33/-3
simplify;
-3(x+9)/-3
Divide the numbers:3/3=1
=x+9
Simplify 33/-3
=-33/3
Divide the numbers 33/3
=-11
x+9=-11
Subtract 9 from both sides
x+9-9=-11-9
Simplify;
x=-20
Helped by none other than the ONE and ONLY #QUEEN aka #DRIPPQUEENMO!